10x-3+9x+7=

Simple and best practice solution for 10x-3+9x+7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-3+9x+7= equation:


Simplifying
10x + -3 + 9x + 7 = 0

Reorder the terms:
-3 + 7 + 10x + 9x = 0

Combine like terms: -3 + 7 = 4
4 + 10x + 9x = 0

Combine like terms: 10x + 9x = 19x
4 + 19x = 0

Solving
4 + 19x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 19x = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 19x = 0 + -4
19x = 0 + -4

Combine like terms: 0 + -4 = -4
19x = -4

Divide each side by '19'.
x = -0.2105263158

Simplifying
x = -0.2105263158

See similar equations:

| -7/6a=28 | | 9x+3=117 | | X^2+3x-6x+3x=49 | | 136+6x=-128-5x | | 3x^3-8x-11=0 | | -35-4x=6-10x | | 11-7x=63-35x | | 117=9 | | 4(x^2+1/x^2)-8(x+1/x)+3=0 | | 3x-5=10-33 | | 4x+x-8+5x+10x=12 | | x^3+11x^2-5x+1=0 | | 10+2t=3t-1 | | 2805739x-45759=583428563957489667 | | 39/49*14/99*27/26 | | 8a-5=4(3a-1) | | -6(3t-5)-4(2t+6)+4t= | | v/3-v/6=2 | | -3(2-9)+13= | | 5/6*6 | | 3(3x-1)=5(2-x)+3 | | x-56409=240021 | | x+5/6=x/2+3/4 | | (-9)(-9)(-9)= | | 5t^2+t-18=0 | | -1=-7x+6 | | 9/48/(-9/8) | | 2x+-2=4 | | (-3)(-5)(-4)(-10)= | | -1=-7x+6y | | y^2+y-0=0 | | x-246=688 |

Equations solver categories